Recognition Based on Paralogism (Aristot. Poet. 1455 a 12–16) - Almazova, Nina (Hyperboreus, 2019)
Classiﬁcation of recognitions in Chapter 16 of the Poetics cannot be based on true or false inferences of the recognizing characters, since reasoning of the same kind (often imperfect from the logical point of view, but still plausible) is required for any discovery in all the examples. Rather it is based on the means of recognition, which is some feature, conduct or saying of the recognized party. Recognition ἐκ συλλογισμοῦ, as all examples but the ﬁrst one show, is founded on a statement (‘enumerating together’) of some unique fatal coincidence by a character going to be recognized, made within hearing of the other. The example from Aeschylus’ Choephori (Poet. 1455 a 4–6) contradicts the context and must be an interpolation. Recognition ἐκ παραλογισμοῦ τοῦ θεάτρου is not a separate type, but a subspecies marked by an impossible or improbable premise (such as the existence of a bow which nobody but Odysseus can bend), which the poet however makes his audience accept, provoking a false inference of the cause from the consequent, as described in 1460 a 18–26. In Odysseus the False Messenger this impossibility was probably made still less believable by a slip on behalf of the author who made his character say that he would recognize the bow which he had never seen. The epithet συνθετή may mean either ‘combined’ with a paralogism of the audience or ‘ﬁctitious’, i. e., based on a ﬁctitious premise.